2017
DOI: 10.4103/2277-9175.221860
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hydroalcoholic Extract of Nigella sativa Seeds on Serum Estradiol and Prolactin Levels and obstetric Criteria due to Hypothyroidism in Rat

Abstract: Background:The aim of this study was investigation of the effects of Nigella sativa (NS) seeds on hypothyroid pregnant rats and their progenies.Materials and Methods:Hypothyroidism was induced by propylthiouracil (PTU) 0.03% in drinking water. Female rats were divided into seven groups: control, PTU, PTU-NS (100, 200, and 400 mg/kg), and NS (100 and 400 mg/kg). All treatments were done 20 days before mating and during pregnancy. The weight of rat dams and progenies, number of progenies and serum T4, estradiol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…( 2016 ) on the ovariectomized rats treated with N. sativa extract showed that the extract of this plant, in a dose鈥恉ependent manner (300 to 1200 mg/kg), reduced menopausal symptoms including uterine weight/edema loss and decreased serum estradiol level and the number of inflammatory cells in the vagina compared with the control group (Parhizkar et al., 2016 ). The doses of 100 to 400 mg/kg of N. sativa extract decreased the serum level of estradiol and increased prolactin in a dose鈥恉ependent manner in pregnant rats with hypothyroidism, which can be due to the stimulatory effects of phytoestrogens of this plant on dopaminergic neurons, reducing the risk of hypothyroidism (Pakdel et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…( 2016 ) on the ovariectomized rats treated with N. sativa extract showed that the extract of this plant, in a dose鈥恉ependent manner (300 to 1200 mg/kg), reduced menopausal symptoms including uterine weight/edema loss and decreased serum estradiol level and the number of inflammatory cells in the vagina compared with the control group (Parhizkar et al., 2016 ). The doses of 100 to 400 mg/kg of N. sativa extract decreased the serum level of estradiol and increased prolactin in a dose鈥恉ependent manner in pregnant rats with hypothyroidism, which can be due to the stimulatory effects of phytoestrogens of this plant on dopaminergic neurons, reducing the risk of hypothyroidism (Pakdel et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pakdel, et al showed that the administration of Nigella sativa at doses of 100 mg/kg, 200 mg/kg, 400 mg/kg in hypothyroidism rats could increase prolactin levels in the 400 mg/kg group [13]. According to research by Sima T, et al, Treatment with thymoquinonee 8 and 16 mg/kg for 30 days in PCOS model mice showed an increase in body weight, ovarian morphology, and ovulation.…”
Section: Study In Humanmentioning
confidence: 99%
“…19 Apart from that, there are other studies from different group of investigators regarding its protective effects against hypothyroidism-associated abnormality in estradiol and prolactin hormone levels in pregnant rats. 20,21 Haridra (Curcuma longa L.)…”
Section: Upakunjika (Nigella Sativa L) Oilmentioning
confidence: 99%
“…Several studies reported that hypothyroidism can actually modulate the antioxidant defense system, with a decrease in body temperature due to hypometabolism. [18][19][20][21][22][23][24][25] Previous studies elucidated the efficiency of curcumin, a common spice in Indian household, in improving the expression of superoxide dismutase (SOD) in the cerebral cortex and cerebellum of the rat brain under PTU-induced hypothyroidism. Induction of hypothyroidism in adult rats by PTU results in intensification of lipid peroxidation (LPO), an indicator of oxidative stress in the cerebellum but not in the cerebral cortex.…”
Section: Upakunjika (Nigella Sativa L) Oilmentioning
confidence: 99%